Autonomy, Participation, and Transparency in SBM Significantly Enhance Teacher Performance: A Multiple Linear Regression Analysis - Dian Andrayani; Sedarmayanti; Dety Mulyanti; Kosasih (Jurnal Isema : Islamic Educational Management, 2026)
This study aims to analyze and measure the partial and simultaneous effects of autonomy (X1), participation (X2), and transparency (X3) in School-Based Management (SBM) on teacher performance (Y) at SD Al-Irhaam, Bandung. A quantitative approach utilizing descriptive and verification methods was adopted. Data collection was carried out by distributing closed questionnaires to 28 teachers as census respondents. Ordinal data gathered from the Likert scale were transformed into interval data using the Method of Successive Interval (MSI) prior to multiple linear regression analysis. The results indicate that partially, autonomy (t = 2.714; p < 0.05), participation (t = 2.408; p < 0.05), and transparency (t = 4.400; p < 0.05) have positive and significant effects on teacher performance. Simultaneously, these three variables exert a significant influence (F = 30.116; p < 0.05) with a coefficient of determination (R^2) of 79.0%. These findings suggest that strengthening independent, participatory, and accountable school governance is an absolute prerequisite for advancing professionalism and instructional effectiveness among teachers in private Islamic educational institutions.